Effects of varying rates of tallgrass prairie hay and wet corn gluten feed on productivity of dairy cows - D.J. Rezac; K.N. Grigsby; Barry J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2010)
Productivity of lactating dairy cows was assessed when fed diets containing wet corn gluten feed (WCGF; Sweet Bran, Cargill Inc.) as the primary energy substrate and prairie hay as the primary source of physically effective neutral detergent fiber (peNDF) compared with a control diet. Treatment diets were: 1) a control diet with 18% alfalfa, 18% corn silage, 33% WCGF, and 15% forage NDF (CON); 2) a diet with 20% tallgrass prairie hay, 46% WCGF, and 13% forage NDF (TPH20); and 3) a diet with 14% tallgrass prairie hay, 56% WCGF, and 9% forage NDF (TPH14). Midway through period 2, the TPH14 treatment diet was discontinued because of numerous cases of diarrhea. Dry matter intake was not altered by treatment. Milk yields were 80.0, 76.3, and 78.5 lb/day for CON, TPH20 and TPH14, respectively; milk yield was greater for CON than TPH20. Milk fat percentage was least for TPH14 with means of 3.47, 3.40, and 2.82% for CON, TPH20, and TPH14, respectively. Fat yield was greater for CON compared with TPH14, but was not different from TPH20. Milk urea nitrogen (MUN) was greatest for TPH20 and least for CON with TPH14 being intermediate, consistent with differences in dietary protein. Efficiencies, expressed as energy corrected milk divided by dry matter intake, were 1.45, 1.40, and 1.30 for CON, TPH20, and TPH14, respectively, and did not differ among diets. These data indicate that TPH14 did not provide adequate peNDF to support normal rumen function in midlactation dairy cows; however, TPH20 offered a feasible diet for use in dairies where high-NDF grass hay and WCGF are available.; Dairy Day, 2010, Kansas State University, Manhattan, KS, 2010; Dairy Research, 2010 is known as Dairy Day, 2010
Keywords: Dairy Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-129-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1039; Dairy; Milk yield; Tall grass prairie hay; Wet corn gluten feed